Oxidation Desulphurization of Heavy Naphtha Improved by Ultrasound Waves - Jima, Bariq Bahmman; Majeed, Najwa Saber (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The oxidation desulphurization assisted by ultrasound waves was applied to the desulphurization of heavy naphtha. Hydrogen peroxide and acetic acid were used as oxidants, ultrasound waves as phase dispersion, and activated carbon as solid adsorbent. When the oxidation desulphurization (ODS) process was followed by a solid adsorption step, the performance of overall Sulphur removal was 89% for heavy naphtha at the normal condition of pressure and temperature. The process of (ODS) converts the compounds of Sulphur to sulfoxides/ sulfones, and these oxidizing compounds can be removed by activated carbon to produce fuel with low Sulphur content. The absence of any components (hydrogen peroxide, acetic acid, ultrasound waves and activated carbon) from the ODS process leading to reduce the performance of removal, hydrogen peroxide was the most crucial factor. The ultrasound waves increase the dispersion of carbon, water and oil phase, promotes the interfacial mass transfer, and this leads to accelerates the reaction. The ultrasound waves did not affect the chemical or physical properties of the fuel. The chemical analysis of treated fuel oil showed that